Standar Operasional Prosedur Unit Simpan Pinjam Sebagai Upaya Peningkatan Kualitas Pelayanan BUMDes - Much Imron; Subadriyah Subadriyah (S1 Accounting Program, Universitas Pamulang, 2020)
Community service activities for BUMDes Tegal Makmur in managing SOP. One of the BUMDes that has been running quite well is the BUMDes Tegal Sambi, Annual District of Jepara. Where in 2017, Village-Owned Enterprises (BUMDes) inaugurated the Tegal Makmur Shop. In 2017, Rp60 million was disbursed for the physical construction of the store. Issues discussed in the management unit, BUMDes are administrative aspects, organizational aspects, and HR aspects. The solutions offered are 1) improvement and administration program, 2) Organization Strengthening Program, 3) BUMDes HR Improvement Program. The Implementation Method is carried out in three panes: 1) Preparation, 2) Implementation, and 3) approval. The result of this service is that the SOP which is used as a purpose of service can be developed and used in the business activities of partners. The benefits of SOP have also been felt by partners.